Molecular characterization of the equine AEG1 locus. - Schambony, Alexandra; et al. (Gene, 2002)
Acidic epididymal glycoprotein 1 (AEG1), also called cysteine-rich secretory protein 1 (CRISP1), is a member of the CRISP protein family which is characterized by 16 conserved cysteine residues at the C-terminus. The CRISP proteins are expressed in the male genital tract and are thought to be involved in sperm-egg fusion. Therefore, their genes are of interest as candidate genes for inherited male fertility dysfunctions and as putative quantitative trait loci for male fertility traits. In this report, the cloning and DNA sequence of 90 kb of horse genomic DNA from equine chromosome 20q22 containing the complete equine AEG1 gene are described. The equine AEG1 gene consists of eight exons spanning 31 kb. Analysis of equine AEG1 transcripts did not reveal any evidence for alternative splicing, however three different transcription start sites are used. The first transcription start site is located 20 nt downstream of a TATA box motif. Reverse transcription polymerase chain reaction analysis demonstrated that AEG1 is expressed in different parts of the epididymis, whereas it is hardly detectable in the testis. The naturally occurring diversity of the equine AEG1 gene in different horse breeds was investigated and several polymorphisms are reported, including one that affects the amino acid sequence. Finally, sequence comparisons revealed that the intronless equine PGK2 gene for the testis-specific phosphoglycerate kinase is located approximately 39 kb downstream of AEG1.